AN ANALYSIS OF CHILD PORNOGRAPHY AND VIRTUAL SEXUAL SOLICITATION - Kumar, Sanjeev; Pallathadka, Harikumar; Kirana Pallathadka, Laxmi (International Journal of Psychosocial Rehabilitation, 2021)
Child pornography on the internet is becoming an increasingly apparent issue in today'ssociety. Child pornographers have discovered a convenient forum for distributing terribleimages of children who have been sexually assaulted due to increased homeComputer use and more easily accessible access to the World Wide Web during the lastdecade. Additionally, police and attorneys worldwide have discovered that identifying andProsecution of cyberchild pornographers has become time-consuming, with a high failure rateof putting offenders in prison. When fighting online child pornography, law enforcementauthorities' techniques presently in use may be deemed archaic and ineffective. This articleexamines the main social, legal, and technical problems that people, legislators, and lawenforcement officials are confronted with regarding cyber child pornography. Thus, thispaper examines how children are exposed to violence through their use of the internet, aswell as the need for parents, schools, government, and all stakeholders to take protective andpreventive measures to ensure children's safety in cyberspace, including throughcomprehensive education and child protection standards.